Histological Investigations on an Intestinal Level in Common Carp, One Summer Old, Fed with Organic Selenium (Selplex) Supplemented Fodder - Aurel Șara; Alina Rodica Ani (Toma); Florin Molnar; Erol Gabor (Scientific Papers Animal Science and Biotechnologies, 2023)
The goal of this research was to analyze the effect of organic Selenium (SelPlex) on the intestinal mucosa and the impact on the growth and consumption performances in one summer old common carp (Cyprinus carpio), Lausitz and Galitian varieties. The research were conducted on a number of 392 fish, Lausitz variety divided in 2 groups and on 192 fish, Galitian variety, divided into 2 groups. The fish were raised in 2 ponds (one pond for the control group and one pond for the experimental group), in a semi-intensive polyculture system. The rearing conditions were identical for the 2 groups. The fodder for the experimental group was supplemented with Selenium (0.03mg/kg fodder). At the end of the experiment, the Selenium supplementation had a positive influence on the height of the intestinal villi. The experimental group (both varieties) showed significant differences compared with the control group. The mean height of the intestinal microvilli from the experimental group, Lausitz variety, was 2.328μm, 0.95% bigger compared to the same variety of the control group. The Galitian variety showed a mean height of the microvilli of 2.227μm, 0.72% biger than the same variety of the control group. This development of the villi structures in the experimental groups led to an increase in the absorption surface of the intestine which explains the accelerated growth and the improvement of the feed conversion ratio.